Silicone composition and its uses
A one-part, room temperature curable ablative silicone composition addresses the limitations of existing ablative coatings by providing a single, thick, VOC-free application with enhanced heat resistance and flexibility, suitable for high-temperature aerospace and rocket applications.
Patent Information
- Application Number
- JP2024525521
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-11-29
- Filing Date
- 2022-11-08
- Publication Date
- 2025-01-07
AI Technical Summary
Existing ablative compositions for thermal protection coatings require multiple applications, long curing times, and often release volatile organic compounds (VOCs), and they lack sufficient heat resistance and flexibility, making them unsuitable for high-temperature applications.
A one-part, room temperature curable and sprayable ablative silicone composition is developed, which is thixotropic and deep cures within 24 hours, using a specific blend of organopolysiloxane, precipitated calcium carbonate, non-fibrous fillers, and a silane crosslinking agent, free of diluents or solvents, and is applied using high shear mixing to achieve a single, thick coating without VOC emissions.
The composition provides a durable, flexible, and heat-resistant ablative coating that can withstand temperatures up to 3000°C, with improved adhesion and reduced curing time, suitable for aerospace and rocket applications, while eliminating VOCs and requiring fewer applications.
Smart Images

Figure 2025500008000001 
Figure 2025500008000002 
Figure 2025500008000003
Abstract
Description
[Technical field]
[0001] The present disclosure generally relates to a method for providing an ablative coating to a substrate using a one-part room temperature curable and sprayable ablative silicone composition that is thixotropic and deep cures within 24 hours to provide an ablative or thermal protective layer on the article. The one-part room temperature curable and sprayable ablative silicone composition is substantially free of diluents or solvents. The ablative or thermal protective coating is designed to provide high heat resistance (i.e., up to or even above (>) 3000°C) or direct flame retardancy suitable for protecting heat-sensitive equipment, for example, in missiles, aircraft and spacecraft, through the conversion of the resulting cured silicone ablative layer to silica / char.
[0002] Conventional methods used to protect substrates from the effects of high temperature heat exposure or flame contact include the use of solid thermal tiles, such as those used on the space shuttle, which are applied to the substrate surface using high temperature adhesives. The tiles are effective as long as they remain attached to the underlying substrate surface, and are known to delaminate from the substrate surface due to both differences in thermal expansion properties between the substrate and the tile, and forces acting on the tile by the high temperature heat source, i.e., rocket engine exhaust. When the tile is removed, the underlying substrate becomes exposed to harmful high temperature heat, which can also act as a propagation point for more tiles to be lost from the surrounding area. Thus, thermal protective coatings and / or layers using ablative materials are increasingly being used.
[0003] Thermally protective coatings and / or layers of ablative material are applied onto a substrate such that the majority of the heating action is on the ablative layer instead of being transferred to the structure of, for example, a missile, aircraft or spacecraft. Substrates of interest are materials exposed to high heat, direct or indirect flame impingement and / or high friction, such as steel structures, cement trenches, rockets, heat shields, rocket engines, missiles, missile nose cones, missile deployment gear, etc. (i.e., hypersonic missiles).
[0004] During use, the outer surface of the ablative coating and / or layer applied on such substrates may gradually carbonize and / or sublimate when subjected to such heating action, while the bulk of the ablative coating and / or layer may undergo pyrolysis releasing the resulting gases. The heat is carried away by the resulting gases, for example from the missile, aircraft or spacecraft structure, thus preventing significant penetration into the substrate (structure) to which the ablative coating and / or layer is applied, thus maintaining the substrate / structure at a safe temperature. The thickness of the ablative coating and / or layer is calculated to be sufficient to withstand the heat encountered during its mission.
[0005] However, many historical ablative compositions rely on epoxy and polyurethane materials that offer only limited heat resistance of about 1000°C to 1500°C and are therefore not suitable for high temperature applications, e.g., above (>) 2000°C; furthermore, they offer poor UV, weather, and acid resistance, can lack flexibility, and can emit toxic fumes upon combustion.
[0006] Conventional ablative coating compositions can be applied onto a substrate by rolling, troweling, painting and / or spraying, with or without volatile organic compounds (VOCs), and can be thixotropic or non-thixotropic.
[0007] Many ablative coatings and / or layers formed from conventional ablative coating compositions need to be cured in situ at high temperatures, i.e., at temperatures higher than the ambient outdoor temperature, and may even require a curing process that includes exposing the applied ablative coating composition to gradually increasing temperatures over a period of time, which makes the use of such ablative coating compositions complicated and time consuming. This is particularly true when the substrate being coated is a large structure, such as a rocket launch pad or the exterior surface of a rocket, which requires that the curing process be carried out by exposing the entire coated surface to the necessary curing heat in a large oven or the like, or by sequentially using locally applied heat sources to cure the coated portions of the substrate.
[0008] Most filled silicone elastomers exhibit at least some tendency to form surface char when exposed to high heat, especially direct or indirect flame impingement, and therefore can be used as silicone ablative compositions. Once cured, the resulting silicone ablative coating and / or layer functions as an ablative in that as the elastomeric material is heated, the original surface material is designed to thermally decompose, resulting in the production of a porous residue or char. The surface of the charred layer can then recede as heating continues. Conventional silicone ablative compositions include two-part hydrosilylation (addition) cure compositions that cure at high temperatures, and two-part condensation cure compositions.
[0009] Furthermore, by utilizing unique fibers to aid in char formation and char retention, prior art silicone ablatives can have unique expanding ablative properties where the ablative bulk actually absorbs the heat of reaction causing the cured bulk to "swell" slightly during ablative action before shrinking during cooling. The fibers form a network within the cured bulk resulting in a brittle char layer. Such compositions are generally applied onto the substrate surface by troweling, which can be a slow process, especially when coating large surface areas.
[0010] Silicone ablative compositions have been prepared for use in spray applications. However, such compositions have typically been diluted with a solvent. While such diluted coating compositions can be used for spraying, they have the disadvantage that they can only produce thin coating thicknesses, e.g., 1.27 mm, before having flow / slump problems (sometimes called creep) due to dilution. Furthermore, while such coatings can be coated onto a substrate surface at thicknesses of up to about 1.27 mm, the diluent contained therein is designed to evaporate as the composition cures, in which case the thickness of the cured coating can be up to about half the thickness of the uncured coating, which tends to require 3-5 repeated applications to build up a suitable thickness of coating ablative over several layers, and each time a new layer is applied, a period of up to 12 hours is required for the coating to be sufficiently cured before a further layer can be overcoated. This of course means that it may take 2 or 3 days for a satisfactory ablative coating to be produced before the next application, and because the diluent is typically an organic solvent, such coatings often emit VOCs during their evaporation during each curing process.
[0011] Therefore, the use of silicone ablative compositions is particularly attractive because they can form thermal ablative coatings with elastomeric properties that provide a degree of flexibility and impact resistance. They also provide protective coatings that have good UV resistance, weather resistance, and acid resistance, and do not emit toxic fumes when exposed to high temperature conditions. However, hydrosilylation-cured silicone compositions are cured at high temperatures (i.e., above room temperature), which may be undesirable in some cases. Silicone condensation-cured compositions cure significantly slower, for example, one-part titanate-cured condensation compositions may require up to 7 days of cure per 6 mm of body depth of uncured material. Tin-cured condensation systems cure in shorter periods of time, but have the disadvantage (in some cases) of reversing reactions (i.e., depolymerization) at temperatures above 80°C.
[0012] Thus, there remains a need for a method of providing an ablative coating to a substrate that includes a condensation curable silicone ablative coating composition that is sprayable, yet sufficiently thixotropic to be applied onto a substrate in a single coat at a thickness of 2.5 mm to 5 mm, and that can be cured at room temperature without the emission of VOCs due to evaporation of the organic diluent during the curing process.
[0013] Provided herein is a method for providing an ablative coating to a substrate, comprising: (I) preparing a one-part room temperature curable and sprayable ablative silicone composition by high shear mixing in a high shear mixer and / or using a twin screw extruder, the one-part room temperature curable and sprayable ablative silicone composition comprising: (a) an organopolysiloxane having the following structure: DZ-(R 1 ) y SiO (4-y) / 2 ) z -SiR 1 2-ZD (Wherein, D is (i)-Si-R n X3-n or (ii) -Si(R 1 )2-O-Si(R 1 )(O-Si(R 1 )2-Z 1 -Si-R n X 3-n )2, Each R 1 are the same or different and are an alkyl group, an alkenyl group, or an aryl group; 1 is a divalent organic group, y has an average value of about 2, z is the number average degree of polymerization and is an integer of at least 50, each X is a hydroxyl group or an alkoxy group, each R is individually selected from alkyl groups, aminoalkyl groups, polyaminoalkyl groups, epoxyalkyl groups, alkenyl groups, or aromatic groups, and n is 0, 1, or 2; (b) At least 15 m, which can be hydrophobized. 2 / g BET surface area of precipitated calcium carbonate; (c) one or more non-fibrous, non-reinforcing fillers; wherein the cumulative weight percent of components (b) and (c) is 40-60% by weight of the composition, and the weight ratio of precipitated calcium carbonate (b) to one or more non-fibrous, non-reinforcing fillers (c) is 1:2 to 1:7. (d) a silane crosslinker having the structure R 7 c -Si-R 6 4-c (In the formula, each R 7 is an alkoxy group, a ketoximino group, or an alkenyloxy group having 1 to 10 carbon atoms, and each R 6 is selected from nonhydrolyzable silicon-bonded organic groups, and c is 2, 3, or 4; (e) a titanate or zirconate condensation catalyst; The composition is substantially free of diluents or solvents; preparing a one-part room temperature curable and sprayable ablative silicone composition resulting from step (I) having an extrusion rate of 1900 to 2600 g / min as measured according to ASTM C1183; (II) spraying the resulting mixture of step (I) onto a substrate surface to produce a thixotropic, curable coating on the substrate having a coating thickness of 2.5 to 5 mm as measured using a wet film comb gauge before any visible indication of slump / flow occurs; (III) curing the composition at room temperature.
[0014] Also provided is an article having an ablative coating obtainable or obtained by the above method.
[0015] Further provided is an article having an ablative coating that is the cured product of a one-part, room temperature curable, sprayable ablative silicone composition, the ablative silicone composition comprising: (a) an organopolysiloxane having the following structure: DZ-(R 1 ) y SiO (4-y) / 2 ) z -SiR 1 2-ZD (Wherein, D is (i)-Si-R n X 3-n or (ii) -Si(R 1 )2-O-Si(R 1 )(O-Si(R 1 )2-Z 1 -Si-R n X 3-n )2, Each R 1 are the same or different and are an alkyl group, an alkenyl group, or an aryl group; 1is a divalent organic group, y has an average value of about 2, z is the number average degree of polymerization and is an integer of at least 50, each X is a hydroxyl group or an alkoxy group, each R is individually selected from alkyl groups, aminoalkyl groups, polyaminoalkyl groups, epoxyalkyl groups, alkenyl groups, or aromatic groups, and n is 0, 1, or 2; (b) At least 15 m, which can be hydrophobized. 2 / g BET surface area of precipitated calcium carbonate; (c) one or more non-fibrous, non-reinforcing fillers; wherein the cumulative weight percent of components (b) and (c) is 40-60% by weight of the composition, and the weight ratio of precipitated calcium carbonate (b) to one or more non-fibrous, non-reinforcing fillers (c) is 1:2 to 1:7. (d) a silane crosslinker having the structure R 7 c -Si-R 6 4-c (In the formula, each R 7 is an alkoxy group, a ketoximino group, or an alkenyloxy group having 1 to 10 carbon atoms, and each R 6 is selected from nonhydrolyzable silicon-bonded organic groups, and c is 2, 3, or 4; (e) a titanate or zirconate condensation catalyst; The one-part, room temperature curable and sprayable ablative silicone composition is substantially free of diluents or solvents; and having an extrusion rate of 1900 to 2600 g / min, as measured according to ASTM C1183; and after spraying onto a substrate surface to produce a thixotropic curable coating on the substrate, having a coating thickness of 2.5 to 5 mm as measured using a wet film comb gauge before any visible indication of slump / flow appears.
[0016] Also provided is the use of a composition comprising: (a) an organopolysiloxane having the following structure: DZ-(R 1 ) ySiO (4-y) / 2 ) z -SiR 1 2-ZD (Wherein, D is (i)-Si-R n X 3-n or (ii) -Si(R 1 )2-O-Si(R 1 )(O-Si(R 1 )2-Z 1 -Si-R n X 3-n )2, Each R 1 are the same or different and are an alkyl group, an alkenyl group, or an aryl group; 1 is a divalent organic group, y has an average value of about 2, z is the number average degree of polymerization and is an integer of at least 50, each X is a hydroxyl group or an alkoxy group, each R is individually selected from alkyl groups, aminoalkyl groups, polyaminoalkyl groups, epoxyalkyl groups, alkenyl groups, or aromatic groups, and n is 0, 1, or 2; (b) At least 15 m, which can be hydrophobized. 2 / g BET surface area of precipitated calcium carbonate; (c) one or more non-fibrous, non-reinforcing fillers; wherein the cumulative weight percent of components (b) and (c) is 40-60% by weight of the composition, and the weight ratio of precipitated calcium carbonate (b) to one or more non-fibrous, non-reinforcing fillers (c) is 1:2 to 1:7. (d) a silane crosslinker having the structure: R 7 c -Si-R 6 4-c (In the formula, each R 7 is an alkoxy group, a ketoximino group, or an alkenyloxy group having 1 to 10 carbon atoms, and each R 6 is selected from nonhydrolyzable silicon-bonded organic groups, and c is 2, 3, or 4; (e) a titanate or zirconate condensation catalyst; The composition is substantially free of diluents or solvents in preparation of an ablative coating on a substrate, and has an extrusion rate of 1900 to 2600 g / min, as measured according to ASTM C1183, and after spraying onto a substrate surface to produce a thixotropic, curable coating on the substrate, has a coating thickness of 2.5 to 5 mm, as measured using a wet film comb gauge, before any visible indication of slump / flow appears.
[0017] High shear mixers are well known and widely used in the chemical industry. High shear mixers disperse or transport one phase or component (liquid, solid, gas) with which is usually immiscible or difficult to mix under high shear mixing into the main continuous phase (liquid). A rotor or impeller, along with a stationary component known as a stator, or an array of rotors and stators, is used either in a tank containing the solution to be mixed or in a pipe through which the solution passes to generate shear. High shear mixers can function in either batch mode or continuous form. One example of a continuous high shear mixer is a twin screw extruder, which is a very efficient high shear mixer that operates continuously. For high shear mixing, the rotation speed of the rotor or screw can be, for example, 500 rpm or more, for example, 1000 rpm or 1500 rpm for a twin screw extruder. In each case, such values are determined by the high shear mixer utilized, but the effect is substantially the same regardless of the type of high shear mixer. Another way to define such a high shear mixer is by a parameter commonly called "tip speed or blade speed," which is a measure of how far a point on the outermost edge of the mixer blade moves in a given amount of time. It is determined by calculating the circumference of the path of the mixer blade in the mixer, i.e., πD (where D is the diameter of the mixer blade), and multiplying it by the rotational speed. Thus, high shear mixing is defined as mixing at 3.25 ms -1 More than or equal to 4.00ms -1 Greater than or equal to 5.00ms -1The mixing may be carried out in a high shear mixer having a tip speed of greater than 1000 rpm. Surprisingly, it has been found that the above compositions are only suitable for the applications herein when mixed under high shear, and when similar compositions are mixed using a low shear mixer, they do not meet the necessary requirements herein.
[0018] The compositions described herein are one-part, room temperature curing, sprayable ablative silicone compositions that upon curing provide an ablative coating on a substrate.
[0019] Typically, the silicone ablative coating is a topcoat on a substrate. It may be applied, for example, over a layer of paint or another coating that has been previously applied to the substrate surface prior to the addition of the ablative layer described herein, or it may be applied directly onto the substrate surface.
[0020] The substrate surface to which the one-part room temperature curable and sprayable ablative silicone composition is applied tends to be the underlying substrate that would otherwise be exposed to the effects of high temperature heat exposure and / or flame contact during use.The articles in which the substrate forms a part may include aerospace vehicles, rocket parts such as nozzle units, combustion chambers and engine casings, reentry spacecraft, missile parts such as missile nose cones, missile and rocket launch pad aircraft parts, heat shields and / or other articles containing critical structural members related to heat generating devices.
[0021] The ablative coatings herein are designed to be sacrificial coatings where the cured bulk releases heat during ablation in the form of oxidized silica "ash". Thus, the bulk loss rate is greater for such sacrificial coatings than intumescent ablatives formulated with unique fibers to aid in char formation and more importantly char retention. The presence of such fibers creates a network within the cured bulk and the resulting char layer is more brittle and durable compared to the surface char produced by the ablative coatings described herein. Typically, the silicone ablative coatings described herein are generally utilized for a single ablative operation, such as a rocket launch, and need to be replaced after each launch. To perform well as an ablative, the coatings provided herein, when coated to about 4.8-5 mm on a ceramic tile and exposed to temperatures of 3000-3500°C for up to 30 seconds by exposure to an acetylene-oxygen torch, preferably have an ablation penetration rate of 0.1-10 mm / sec, as determined by taking thickness measurements using a set of calipers before and after heat exposure. The difference before and after was then divided by the exposure time to obtain the penetration rate. Similarly, it should have a bulk weight loss of between 0.1 and 10 g / sec, as measured by determining the weight of the coating before and after a given period of exposure, e.g., 10 seconds, to an acetylene-oxygen torch to determine the weight loss. Similarly, ceramic tile substrates treated with an ablative coating using the coating compositions described herein should withstand exposure times of 1 to 20 seconds, alternatively 5 to 20 seconds, alternatively 7.5 to 20 seconds.
[0022] The one-part, room temperature curable and sprayable ablative silicone compositions herein preferably achieve one or more of the following: (1) Having a deep hardening depth of 0.25 cm to 0.6 cm in 24 hours; (2) be sprayable, i.e., capable of being spray coated using suitable spray equipment; (3) have a stable viscosity upon aging, i.e., the viscosity after aging for 2 weeks at 50°C is less than twice its original viscosity, so that the ablative coating composition can be pumped through an acceptable size hose system without premature curing, for example through a long main hose, e.g., a hose that is at least 6m long and about 1 cm in diameter, as well as through a suitable light-weight whip hose used between said main coating hose and the spray gun. (4) Having an acceptable long shelf life at room temperature for application by the spray operation, e.g., at least 6 months, alternatively at least 9 months. (5) There are no solvents or diluents in the one-part room temperature curable and sprayable ablative silicone compositions, i.e., there are no volatile organic compounds (VOCs) present (other than trace impurities) in the one-part room temperature curable and sprayable ablative silicone compositions. (6) Sufficiently thixotropic for both horizontal and vertical applications, i.e., free of unacceptable levels of flow / slump after a single spray coating event in the range of 2.5 to 5 mm, e.g., 2.5 mm to 4.45 mm.
[0023] From the viewpoint of curing, these one-part room temperature curable and sprayable ablative silicone compositions have the advantage of curing at room temperature and adhering to substrate at room temperature compared to hydrosilylation compositions.They are also more resistant to contaminants than hydrosilylation cured silicones that use platinum-based catalysts.Furthermore, considering that one-part room temperature curable and sprayable ablative silicone compositions do not contain tin-based catalysts, they do not revert after curing at high temperatures.
[0024] The one-part room temperature curable and sprayable ablative silicone composition utilized herein comprises components (a)-(e) as described above, each of which is discussed in more detail below.
[0025] Organopolysiloxane (a) The organopolysiloxane (a) has the following structure: DZ-(R 1 ) y SiO (4-y) / 2 ) z -SiR 1 2-ZD In the formula, D is (i)-Si-R n X 3-n or (ii) -Si(R 1 )2-O-Si(R 1 )(O-Si(R 1 )2-Z 1 -Si-R n X 3-n )2, Each R 1 are the same or different and are an alkyl group, an alkenyl group, or an aryl group; 1 is a divalent organic group, y has an average value of 1.8 to 2.2, z is the number average degree of polymerization and is an integer of at least 50, each X is a hydroxyl group or an alkoxy group, each R is individually selected from an alkyl group, an aminoalkyl group, a polyaminoalkyl group, an epoxyalkyl group, an alkenyl group, or an aromatic group, and n is 0, 1, or 2.
[0026] Each R 1 are the same or different and are alkyl, alkenyl or aryl groups, or R 1 may be selected from an alkyl group having 1 to 6 carbons, an alkenyl group having 2 to 6 carbons, or an aryl group having 6 to 12 carbons; or R 1 may be selected from methyl, ethyl, octyl, trifluoropropyl, vinyl and phenyl groups.
[0027] Each Z and Z 1 is a saturated divalent organic group or, independently, an alkylene group having 2 to 10 carbons, such as ethylene (-CH-CH-). 1 is preferably linear, but may contain some branching if desired.
[0028] The average value of y is 1.8 to 2.2. Typically, each y is 2 (i.e., the siloxane units are D units), but some branching may occur, i.e., y is 3 (T units) or y is 4 (Q units). The siloxy units may be described by shorthand nomenclature, i.e., "M", "D", "T", and "Q", where R' is an organic group, e.g., a methyl group. M units are R'3SiO 1 / 2 and the D unit corresponds to the siloxy unit R'SiO 2 / 2 and the T unit corresponds to the siloxy unit R'SiO 3 / 2 and the Q unit corresponds to the siloxy unit SiO 4 / 2 is equivalent to.
[0029] The subscript z is the number average degree of polymerization and is an integer of at least 50. The degree of polymerization (DP) in a silicone macromolecule or polymer or oligomer molecule, in this case diorganosiloxane (a), is usually defined herein as z, as the number of repeating monomer units in the macromolecule or polymer or oligomer molecule, for example in this case diorganosiloxane (a). Synthetic polymers essentially consist of a mixture of macromolecular species having different degrees of polymerization and therefore different molecular weights. There are different types of average polymer molecular weights, which can be measured in different experiments. The two most important average polymer molecular weights are the number average molecular weight (M n ) and weight average molecular weight (Mw). n The and Mw values can be measured by gel permeation chromatography (GPC). This technique is standard and gives Mw (weight average molecular weight), Mn (number average molecular weight), and polydispersity index (PI). DP=Mn / Mu, where Mn is the number average molecular weight as measured by GPC using triple detection and polystyrene calibration standards. Mu is the molecular weight of the monomer unit. PI=Mw / Mn. The higher the DP, the higher the viscosity.
[0030] The value of z (i.e., the approximate number average degree of polymerization) is usually significantly greater than 50, typically a value that places the organopolysiloxane (a) within the desired viscosity range; for example, z may be at least 200, alternatively in the range of 200 to 1500, alternatively in the range of 200 to 1000, alternatively in the range of 200 to 700. It may be calculated from determining the number average molecular weight (Mn) value using gel permeation chromatography (GPC), for example, by using a Waters 2695 Separations Module equipped with a vacuum degasser, and a Waters 2414 refractive index detector (Waters Corporation of MA, USA). Analysis was performed using certified grade toluene flowing at 1.0 mL / min as the eluent, using polystyrene standards. Data collection and analysis were performed using Waters Empower™ GPC software (Waters Corporation of MA, USA).
[0031] Each X group can be the same or different and can be a hydroxyl group or an alkoxy group. Exemplary alkoxy groups are methoxy, ethoxy, propoxy, butoxy, isobutoxy, pentoxy, hexoxy and 2-ethylhexoxy groups; dialkoxy groups such as methoxymethoxy or ethoxymethoxy, and alkoxyaryloxy groups such as ethoxyphenoxy. Most preferred alkoxy groups are methoxy or ethoxy. Preferably, each X is an alkoxy group.
[0032] Each R is individually selected from an alkyl group, an aminoalkyl group, a polyaminoalkyl group, an epoxyalkyl group, an alkenyl group, or an aromatic group, or an alkyl group having 1 to 12 carbons; and an alkenyl group having 2 to 12 carbons, or an aromatic group having 6 to 12 carbons; or each R is selected from a methyl group, an ethyl group, an octyl group, a vinyl group, an allyl group, and a phenyl group.
[0033] The subscript n is 0, 1 or 2, alternatively 0 or 1, alternatively 0.
[0034] Organopolysiloxane (a) may be present in an amount from 35% to 60% by weight of the composition, alternatively from 35% to 55% by weight of the composition.
[0035] Precipitated calcium carbonate (b) Precipitated calcium carbonate (b) is at least 15 m 2 The precipitated calcium carbonate (b) may be any suitable precipitated calcium carbonate having a BET surface area of at least 15 m / g, which may be hydrophobically treated and which functions as a reinforcing filler in the composition. Typically, the precipitated calcium carbonate (b) has a surface area of at least 15 m, measured according to the BET method in accordance with ISO 9277:2010. 2 / g, or 15 to 50 m 2 / g, or 15-25m 2 Typically, the precipitated calcium carbonate (b) is present in the one-part room temperature vulcanizable and sprayable ablative silicone composition in an amount of about 5 to 25% by weight of the composition, alternatively about 5 to 20% by weight of the composition, provided that the cumulative weight percent of components (b) and (c) is 40 to 60% by weight of the composition, and the weight ratio of precipitated calcium carbonate (b) to one or more non-fibrous, non-reinforcing fillers (c) is 1:2 to 1:7.
[0036] For example, the precipitated calcium carbonate reinforcing fillers (b) can be hydrophobized with one or more fatty acids, for example fatty acids such as stearic acid or fatty acid esters such as stearates, or with organosilanes, organosiloxanes, or organosilazanes, for example hexaalkyldisilazanes or short chain siloxanediols, to make them hydrophobic, thereby making it easier to handle and obtain a homogeneous mixture with other adhesive components. The surface treatment of the fillers makes them easily wetted with the organopolysiloxane (a). These surface-modified fillers do not harden and can be homogeneously incorporated into the organopolysiloxane (a). This results in improved room temperature mechanical properties of the one-part room temperature curable and sprayable ablative silicone composition. The fillers can be pretreated or can be treated in situ when mixed with the organopolysiloxane (a).
[0037] Non-fibrous, non-reinforcing fillers (c) Such fillers are believed to have a low aspect ratio (ratio of length to diameter) of 1 to 10 (which can be measured using transmission electron microscopy, but is generally identified herein from literature references or supplier data) and can include, for example, zeolites, sericite, kaolin, mica, clay, bentonite, asbestos, talc, and silicates such as alumina silicate, metal compounds such as alumina, magnesium oxide, zirconium oxide, titanium oxide, and iron oxide, ground calcium carbonate, magnesium carbonate, dolomite, sulfates such as calcium sulfate and barium sulfate, glass flakes, glass beads, ceramic beads, mica, boron nitride, and silicon carbide.
[0038] Whenever deemed necessary, one or more non-fibrous, non-reinforcing fillers (c) may also be treated as described above for reinforcing filler (b) to render them hydrophobic, thereby facilitating handling and obtaining a homogeneous mixture with the other components. As in the case of reinforcing filler (b), the surface treatment of the non-reinforcing fillers makes them easily wetted by organopolysiloxane (a). Preferably, the non-fibrous, non-reinforcing filler (c) is ground calcium carbonate. For the avoidance of doubt, non-reinforcing fillers are typically low-cost components that are often used to reduce the overall cost of the material. Their presence may provide some improvement in mechanical properties, but this is much less than the reinforcing fillers contribute.
[0039] The cumulative weight percent of components (b) and (c) is 40-60% by weight of the one-part room temperature curable and sprayable ablative silicone composition, alternatively 45-60% by weight of the composition, and the weight ratio of precipitated calcium carbonate (b) to one or more non-fibrous, non-reinforcing fillers (c) is 1:2 to 1:7.
[0040] In one embodiment, the one or more non-fibrous, non-reinforcing fillers (c) comprise or consist of ground calcium carbonate. Thus, when the one or more non-fibrous, non-reinforcing fillers (c) consist of ground calcium carbonate, the weight ratio of precipitated calcium carbonate (b):ground calcium carbonate is from 1:2 to 1:7.
[0041] Silane Crosslinker (d) The silane crosslinker (d) has the structure: R 7 c -Si-R 6 4-c In the formula, each R 7 is an alkoxy group, a ketoximino group, or an alkenyloxy group having 1 to 10 carbon atoms, and each R 6 is selected from nonhydrolyzable silicon-bonded organic groups; and c is 2, 3, or 4.
[0042] The crosslinking agent (d) utilized herein has the structure R 7 c -Si-R 6 4-c wherein each R 7 is an alkoxy group having 1 to 10 carbons, and each R 6 is selected from nonhydrolyzable silicon-bonded organic groups; and c is 2, 3, or 4.
[0043] Each R 7 may be, for example, an alkoxy group having 1 to 10 carbons, or methoxy, ethoxy, propoxy, isopropoxy, butoxy, t-butoxy, pentoxy (amyloxy), isopentoxy (isoamyloxy), hexoxy, and isohexoxy; alternatively, methoxy, ethoxy, propoxy; ketoximino groups (e.g., dimethyl ketoximo, and isobutylketoximino); or alkenyloxy groups (e.g., isopropenyloxy and 1-ethyl-2-methylvinyloxy). In one embodiment, all occurrences of R 7 The groups are the same and preferably are all alkoxy groups, especially methoxy or ethoxy groups, or methoxy groups.
[0044] Each R 6 The group may be any suitable non-hydrolyzable silicon-bonded organic group, such as alkyl groups having 1 to 6 carbons (e.g., methyl, ethyl, propyl, and butyl); alkenyl groups having 2 to 6 carbons (e.g., vinyl and allyl), cycloalkyl groups (e.g., cyclopentyl and cyclohexyl); aryl groups (e.g., phenyl and tolyl); and aralkyl groups (e.g., 2-phenylethyl).
[0045] It will be appreciated that subscript c can be 2, 3 or 4. Typically, crosslinker (d) may function as a crosslinker only if organopolysiloxane (a) contains more than two -OH or hydrolyzable groups per molecule when subscript c is 2, otherwise crosslinker (d) merely causes chain extension and does not function as a crosslinker. Preferably, subscript c is either 3 or 4 for crosslinking purposes, although it should be understood that in some cases it is desirable to include a fraction of di(alkoxy)functional silanes (c=2) in a mixture with tri- or tetrafunctional alkoxysilanes (c=3 or 4) to impart chain extension and flexibility.
[0046] Silanes that may be used as crosslinking agents (d) include bis(trimethoxysilyl)hexane, 1,2-bis(triethoxysilyl)ethane, alkyltrialkoxysilanes such as methyltrimethoxysilane (MTM) and methyltriethoxysilane, alkenyltrialkoxysilanes such as vinyltrimethoxysilane and vinyltriethoxysilane, isobutyltrimethoxysilane (iBTM). Other suitable silanes include ethyltrimethoxysilane, phenyltrimethoxysilane, 3,3,3-trifluoropropyltrimethoxysilane, tetramethoxysilane, tetraethoxysilane (tetraethylorthosilicate), tetrapropoxysilane (tetrapropylorthosilicate) and tetrapentoxysilane (tetraamylorthosilicate); or alternatively alkoxytrioximosilanes, alkenyltrioximosilanes, methyltris(methylethylketoximo)silane, vinyl-tris-methylethylketoximo)silane, methyltris(methylethylketoximino)silane, alkenylalkyldialkoxysilanes such as vinylmethyldimethoxysilane, vinylethyldimethoxysilane, vinylmethyldiethoxysilane, vinylethyldiethoxysilane, alkenylalkyldioximosilanes such as vinylmethyldioximosilanes, vinylethyldioximosilanes, vinylethyldioximosilanes and / or methylphenyldimethoxysilane. In one embodiment, the crosslinker comprises or consists of methyltrimethoxysilane. The crosslinker (d) used may also comprise any combination of two or more of the above. The composition may comprise 1-15 wt% of crosslinker (d), alternatively 1.5-15 wt% of crosslinker (d), alternatively 1.75-10 wt% of crosslinker (d).
[0047] Titanate or zirconate condensation reaction catalyst (e) The titanate or zirconate condensation catalyst (e) can be selected from titanates or zirconates. The titanate-based catalyst and / or zirconate-based catalyst (e) has the general formula Ti[OR22 ]4 or Zr[OR 22 ]4[In the formula, each R 22 R represents a monovalent, primary, secondary, or tertiary alkyl group which may be the same or different and may be linear or branched having 1 to 10 carbon atoms. Optionally, the titanates and / or zirconates may contain partially unsaturated groups. 22 Examples of R include, but are not limited to, methyl, ethyl, propyl, isopropyl, butyl, tertiary butyl, and branched secondary alkyl groups such as 2,4-dimethyl-3-pentyl. 22 If the same, R 22 is an isopropyl group, a branched secondary alkyl group or a tertiary alkyl group, in particular a tertiary butyl group. Examples of suitable titanates include tetra-n-butyl titanate, tetra-t-butyl titanate, titanium tetrabutoxide, and tetraisopropyl titanate. Examples of suitable zirconates include tetra-n-propyl zirconate, tetra-n-butyl zirconate, and zirconium diethyl citrate.
[0048] Alternatively, the titanate and / or zirconate may be chelated. Chelation may be by any suitable chelating agent, such as an alkyl acetylacetonate, e.g., methyl or ethyl acetylacetonate. Alternatively, the titanate may be a monoalkoxy titanate, resulting in a triple chelating agent, e.g., 2-propanolate, trisisooctadecanoato titanate, or diisopropyl diethyl acetoacetate titanate.
[0049] Alkoxy titanium compounds and alkoxy zirconium compounds, preferably the former, are suitable catalysts for curing one-component moisture-curable silicone compositions via skin or diffusion curing mechanisms. They are typically available in one-component compositions that are applied in layers thinner than 15 mm (layers thicker than 15 mm are known to result in uncured material deep inside the material). Skin or diffusion curing (e.g. moisture / condensation) occurs by the formation of a cured skin at the composition / air interface after the sealant / encapsulant is applied onto the substrate surface. After the formation of the surface skin, the cure rate depends on the diffusion rate of moisture from the sealant / encapsulant-air interface to the interior (or core), as well as the diffusion of condensation reaction by-products / emissions from the interior (or core) to the exterior (or surface) of the material, and the gradual thickening of the cured skin from the exterior / surface to the interior / core over time.
[0050] The catalyst (e) is present in the composition in any suitable catalytic amount, for example from about 0.2 to 2% by weight of the composition.
[0051] Optional Additives The one-part room temperature curable and sprayable ablative silicone compositions described herein may also include one or more optional additives, which may include, but are not limited to, plasticizers / extenders, adhesion promoters, chain extenders pigments, rheology modifiers, heat stabilizers, flame retardants, UV stabilizers, and fungicides and / or biocides.
[0052] Plasticizers / Extenders The one-part room temperature curable and sprayable ablative silicone composition may also contain one or more liquid plasticizers / extenders (sometimes called processing aids) in the form of silicone or organic fluids that are non-reactive with all of the above components (a)-(e).
[0053] Examples of non-reactive silicone fluids useful as plasticizers that can be incorporated into the one-part room temperature curable and sprayable ablative silicone compositions include polydiorganosiloxanes, such as polydimethylsiloxanes having terminal triorganosiloxy groups, where the organic substituents are, for example, methyl, vinyl, or phenyl groups, or combinations of these groups. Such polydimethylsiloxanes can have, for example, viscosities of about 5 to about 100,000 mPa.s at 25° C.
[0054] Alternatively, compatible organic plasticizers may be used in addition to or in place of the silicone fluid plasticizers, including dialkyl phthalates (wherein the alkyl group can be linear and / or branched and contains from 6 to 20 carbon atoms) such as dioctyl phthalate, dihexyl phthalate, dinonyl phthalate, didecyl phthalate, and other phthalates, and related adipate, azelate, oleate, and sebacate esters; polyols such as ethylene glycol and its derivatives; and organic phosphates such as tricresyl phosphate and / or triphenyl phosphate may also be used if compatible with the composition.
[0055] Examples of extenders for use in the one-part room temperature curable and sprayable ablative silicone compositions herein include mineral oil-based (typically petroleum-based) paraffinic hydrocarbons, mixtures of paraffinic and naphthenic hydrocarbons, paraffinic oils including cyclic and non-cyclic paraffins, and hydrocarbon fluids including naphthenes, polycyclic naphthenes, and paraffins, or polyalkylbenzenes, such as heavy alkylates (alkylated aromatic materials remaining in refineries after petroleum distillation). Examples of such extenders are discussed in GB 2424898, the contents of which are incorporated herein by reference.
[0056] If present, the plasticizer or bulking agent content is present in an amount of >0-10% by weight of the composition.
[0057] Adhesion promoter Suitable adhesion promoters are of the formula R 14 h Si(OR 15 ) (4-h) where subscript h is 1, 2, or 3, or h is 3. 14 is independently selected from an epoxy functional group such as glycidoxypropyl or (epoxycyclohexyl)ethyl, an amino functional group such as aminoethylaminopropyl or aminopropyl, a mercapto functional group such as methacryloxypropyl; mercaptopropyl, or an unsaturated organic group. 15 R is independently an unsubstituted saturated hydrocarbon group having at least one carbon atom. 15 R may have 1 to 4 carbon atoms, alternatively 1 to 2 carbon atoms. 15 Examples of alkoxysilanes include methyl, ethyl, n-propyl, and isopropyl.
[0058] Examples of suitable adhesion promoters include glycidoxypropyltrimethoxysilane, and combinations of glycidoxypropyltrimethoxysilane with aluminum or zirconium chelates; aminoalkylalkoxysilanes, such as 3-aminopropyltriethoxysilane, epoxyalkylalkoxysilanes, such as 3-glycidoxypropyltrimethoxysilane and mercaptoalkylalkoxysilanes, and the reaction products of ethylenediamine and silyl acrylate. Silicon-containing isocyanurates, such as 1,3,5-tris(trialkoxysilyl)isocyanurates, may also be used. Further suitable adhesion promoters include the reaction products of epoxyalkylalkoxysilanes, such as 3-glycidoxypropyltrimethoxysilane, with amino-substituted alkoxysilanes, such as 3-aminopropyltrimethoxysilane, and optionally with alkylalkoxysilanes, such as methyltrimethoxysilane.
[0059] Alternatively, the adhesion promoter may be a diaminosilane adhesion promoter having a structure according to the following formula: R 4 t (R'O) 3-t Si-Z 2 -N(H)-(CH2) m -NH2 In the formula, R 4 is an alkyl group containing 1 to 10 carbon atoms, or R 4 is an alkyl group containing 1 to 6 carbon atoms, or R 4 is a methyl or ethyl group. Each R' may be the same or different, and each R' may be the same or different, and is H or R 4 or each R' is R 4 In one alternative, the two R' groups are the same. When the two R' groups are the same, they are preferably methyl or ethyl groups. Z 2 is a straight or branched chain alkylene group having 2 to 10 carbons, or 2 to 6 carbons, for example, Z 2 can be a propylene, butylene, or isobutylene group. The subscript m can be from 2 to 10, in one alternative m can be from 2 to 6, in another alternative m can be from 2 to 5, and in yet a further alternative m can be 2 or 3, or m is 2. An example is N-(3-(trimethoxysilyl)propyl)-1,2-ethanediamine. When present, the adhesion promoter can be present in an amount of 0.01% to 2% by weight, alternatively 0.05 to 2% by weight, alternatively 0.05 to 1.5% by weight (based on the weight of the one-part room temperature vulcanizable and sprayable ablative silicone composition) based on the weight of the total composition when mixed.
[0060] Chain extender Chain extenders may include difunctional silanes that extend the length of the polysiloxane polymer chains before crosslinking occurs, thereby reducing the elongation of the cured elastomer. Chain extenders and crosslinkers compete for reaction with the functional polymer ends, and to obtain significant chain extension, the reactivity of the difunctional silane must be substantially higher than the reactivity of the trifunctional crosslinker employed. Suitable chain extenders include diamidosilanes (such as dialkyldiacetamidosilanes or alkenylalkyldiacetamidosilanes, in particular methylvinyldi(N-methylacetamido)silane or dimethyldi(N-methylacetamido)silane), diacetoxysilanes (such as dialkyldiacetoxysilanes or alkylalkenyldiacetoxysilanes), diaminosilanes (such as dialkyldiaminosilanes or alkylalkenyldiaminosilanes), dialkoxysilanes (such as dimethoxydimethylsilane, diethoxydimethylsilane, etc.), and α-aminoalkyldialkoxyalkylsilanes, polydialkylsiloxanes having a degree of polymerization of 2 to 25 and having at least three acetamido, acetoxy, amino, alkoxy, amido or ketoximo substituents per molecule, and diketoximinosilanes (such as dialkyldiketoximinosilanes and alkylalkenyldiketoximinosilanes).
[0061] Pigments The one-part room temperature curable and sprayable ablative silicone composition described herein may further include one or more pigments and / or colorants that can be added if desired. The pigments and / or colorants can be colored, white, black, metallic effect, and luminescent, such as fluorescent and phosphorescent. If necessary, pigments are utilized to color the one-part room temperature curable and sprayable ablative silicone composition. Any suitable pigment may be utilized as long as it is compatible with the composition herein. In the one-part room temperature curable and sprayable ablative silicone composition, pigments and / or colored (non-white) fillers, such as carbon black, can be utilized in the composition to color the ablative coating if desired.
[0062] Suitable white pigments and / or colorants include titanium dioxide, zinc oxide, lead oxide, zinc sulfide, lithopone, zirconium oxide, and antimony oxide.
[0063] Suitable non-white inorganic pigments and / or colorants include, but are not limited to, iron oxide pigments such as goethite, lepidocrite, hematite, maghemite, and magnetite, black iron oxide, yellow iron oxide, brown iron oxide, and red iron oxide; blue iron pigments; chromium oxide pigments; cadmium pigments such as cadmium yellow, cadmium red, cadmium cinnabar; bismuth pigments such as bismuth vanadate and bismuth vanadate molybdate; mixed metal oxide pigments such as cobalt titanate green; chromate pigments and molybdate pigments such as chrome yellow, molybdate red, and molybdate orange; ultramarine pigments; cobalt oxide pigments; nickel antimony titanate; lead chromium; carbon black; lamp black, and metallic effect pigments such as aluminum, copper, copper oxide, bronze, stainless steel, nickel, zinc, and brass.
[0064] Suitable organic non-white pigments and / or colorants include phthalocyanine pigments such as phthalocyanine blue and phthalocyanine green; monoarylide yellow, diarylide yellow, benzimidazolone yellow, heterocyclic yellow, DAN orange, quinacridone pigments such as quinacridone magenta and quinacridone violet; organic reds including metallized azo reds and non-metallized azo reds and other azo pigments, monoazo pigments, diazo pigments, azo pigment lakes, β-naphthol pigments, naphthol AS pigments, benzimidazolone pigments, diazo condensed pigments, isoindolinone and isoindoline pigments, polycyclic pigments, perylene and perinone pigments, thioindigo pigments, anthrapyrimidone pigments, flavanthrone pigments, anthanthrone pigments, dioxazine pigments, triarylcarbonium pigments, quinophthalone pigments, and diketopyrrolopyrrole pigments.
[0065] Rheology Modifiers The rheology control agent that may be incorporated into the one-part room temperature curable and sprayable ablative silicone composition according to the present invention includes silicone organic copolymers based on polyether or polyester polyols (such as those described in GB 0802233), polyethylene glycols, polypropylene glycols, ethoxylated castor oil, oleic acid ethoxylates, alkylphenol ethoxylates, copolymers or non-ionic surfactants selected from the group consisting of ethylene oxide and propylene oxide, and silicone polyether copolymers; and silicone glycols.For some systems, these rheology control agents, especially the copolymers of ethylene oxide and propylene oxide, and silicone polyether copolymers, can enhance the adhesion of the sealant to the substrate.
[0066] Heat stabilizer Examples of heat stabilizers include metal compounds such as red iron oxide, yellow iron oxide, ferric hydroxide, cerium oxide, cerium hydroxide, lanthanum oxide, copper phthalocyanine, aluminum hydroxide, fumed titanium dioxide, iron naphthenate, cerium naphthenate, cerium dimethylpolysilanolate, and acetylacetone salts of metals selected from copper, zinc, aluminum, iron, cerium, zirconium, titanium, etc. The amount of heat stabilizer, when present in the one-part room temperature curable and sprayable ablative silicone composition, can range from 0.01 to 1.0 weight percent of the composition.
[0067] Flame retardants Flame retardants may include aluminum trihydroxide and magnesium dihydroxide, iron oxide, triphenyl phosphate, dimethyl methyl phosphonate, tris(2,3-dibromopropyl)phosphate (brominated tris), halogenated flame retardants such as chlorinated paraffins and hexabromocyclododecane, and mixtures or derivatives thereof.
[0068] Antioxidants Any suitable antioxidant may be utilized if deemed necessary. Examples include ethylene bis(oxyethylene)bis(3-tert-butyl-4-hydroxy-5(methylhydrocinnamate), 36443-68-2; tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane, 6683-19-8; octadecyl[3,5-di-tert-butyl-4-hydroxyhydroxycinnamate, 2082-79-3; N,N'-hexamethylene-bis(3, 5-Di-tert-butyl-4-hydroxyhydroxycinnamamide), 23128-74-7; 3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid, C7-9 branched alkyl ester, 125643-61-0; N-phenylbenzenamine, reaction products with 2,4,4-trimethylpentene, 68411-46-1; Mention may be made, for example, of the antioxidants sold under the name Irganox (trademark) by BASF.
[0069] UV and / or light stabilizers UV and / or light stabilizers may include, for example, benzotriazole-based ultraviolet absorbers and / or hindered amine light stabilizers (HALS), such as the TINUVIN™ product line from Ciba Specialty Chemicals Inc.
[0070] Biocides Biocides may also be utilized in the one-part room temperature curable and sprayable ablative silicone composition, if desired. It should be noted that the term "biocide" is intended to encompass bactericides, fungicides, algaecides, and the like. Suitable examples of useful biocides that can be utilized in the one-part room temperature curable and sprayable ablative silicone composition include, for example, the following: Carbamates (such as methyl-N-benzimidazol-2-ylcarbamate (carbendazim) and other suitable carbamates), 10,10'-oxybisphenoxyarsine, 2-(4-thiazolyl)-benzimidazole, N-(fluorodichloromethylthio)phthalimide, diiodomethyl p-tolylsulfone, when appropriate in combination with UV stabilizers, 2,6-di(tert-butyl)-p-cresol, 3-iodo-2-propynyl butylcarbamate (IPBC), zinc 2-pyridinethiol-1-oxide, triazolyl compounds and isothiazolinones such as 4,5-dichloro-2-(n-octyl)-4-isothiazolin-3-one (DCOIT), 2-(n-octyl) 4-isothiazolin-3-one (OIT), and n-butyl-1,2-benzisothiazolin-3-one (BBIT). Other biocides may include, for example, zinc pyridinethione, 1-(4-chlorophenyl)-4,4-dimethyl-3-(1,2,4-triazol-1-ylmethyl)pentan-3-ol and / or 1-[[2-(2,4-dichlorophenyl)-4-propyl-1,3-dioxolan-2-yl]methyl]-1H-1,2,4-triazole.
[0071] Thus, a one-part room temperature curable and sprayable ablative silicone composition may comprise a suitable combination of the following: an organopolysiloxane (a) in an amount of 35% to 60% by weight of the composition, alternatively 35% to 55% by weight of the composition; precipitated calcium carbonate (b) and a non-fibrous, non-reinforcing filler (c), preferably ground calcium carbonate, wherein the cumulative weight percent of components (b) and (c) is from 40 to 60 weight percent of the one-part room temperature vulcanizable and sprayable ablative silicone composition, alternatively from 45 to 60 weight percent of the composition, and the weight ratio of precipitated calcium carbonate (b):one or more non-fibrous, non-reinforcing fillers (c) is from 1:2 to 1:7; a silane crosslinker (d) in an amount of 1 to 15% by weight of the composition, alternatively from 1.5 to 15% by weight of the composition, alternatively from 1.75 to 10% by weight of the composition; and A suitable catalytic amount of a titanate or zirconate condensation catalyst (e), for example about 0.2 to 2% by weight of the composition.
[0072] The one-part room temperature curable and sprayable ablative silicone composition may further comprise one or more of the additives identified above, however the total weight percent of any composition is 100 weight percent.
[0073] Preferably, the one-part room temperature curable and sprayable ablative silicone composition prepared under high shear in the high shear mixer has a viscosity of from 40 Pa.s to 125 Pa.s, alternatively from 40 Pa.s to 100 Pa.s, measured at 25°C using a Brookfield™ DV-II+Pro programmable viscometer using spindle 7 at a shear rate of 10 rpm.
[0074] A thixotropic curable coating on a substrate is made from a one-part room temperature curable and sprayable ablative silicone composition after mixing under high shear to provide a coating thickness of 2.5-5mm deep, alternatively 2.5-4.45mm deep, as measured using a wet film comb gauge, before any visible indication of slump / flow / creep appears. (For the avoidance of doubt, wet film comb gauges are also known as notch gauges. These are formed on the edge of a piece of material such that each notch has a different clearance from a reference shoulder to its adjacent and is used to determine film thickness.)
[0075] The method for providing a substrate having an ablative coating as described herein comprises the steps of: (I) Preparing a one-part room temperature vulcanizable and sprayable ablative silicone composition as described above by mixing in a suitable high shear mixer. Feeding the resulting mixture of step (I), i.e., the one-part room temperature curable and sprayable ablative silicone composition, to a spray gun via a suitable hose arrangement. The one-part room temperature curable and sprayable ablative silicone composition resulting from step (I) has an extrusion rate of 1900 to 2600 g / min as measured according to ASTM C1183. (II) spraying the resulting mixture of step (I) onto a substrate surface to produce a thixotropic, curable coating on the substrate having a coating thickness of 2.5-5 mm as measured using a wet film comb gauge before any visible indication of slump / flow / creep occurs; and (III) curing the composition at room temperature.
[0076] The one-part room temperature curable and sprayable ablative silicone composition resulting from the high shear mixing of step (I) has an extrusion rate of 1900 to 2600 g / min, alternatively 1900 to 2500 g / min, as measured according to ASTM C1183.
[0077] The one-part room temperature curable and sprayable ablative silicone composition is prepared using a suitable high shear mixer, such as a twin screw extruder, and a high shear batch mixer, such as a planetary mixer and a kneader type mixer. The one-part room temperature curable and sprayable ablative silicone composition herein is designed to be pumped to a spray gun and then sprayable through a spray gun, and therefore must have a sufficiently low viscosity so that it can be pumped through a hose system or the like, and can be sprayed using any suitable technique, and is designed to be applied to form a single layer that is sufficiently thixotropic to be of suitable thickness, for example, 2.5 mm to 5 mm, or 2.5 mm to 4.45 mm thick, without significant flow when applied either horizontally or vertically on a substrate.
[0078] The amounts of components used in the compositions described herein are selected such that, despite being titanate and / or zirconate cured, the coating deep cures at room temperature within 24 hours at room temperature, which is much faster than many one-part compositions that use such catalysts and may be due in part to the reactivity of the organopolysiloxane (a).
[0079] It has been found that in step (I), by high shear mixing the components described hereinabove, one-part room temperature curable and sprayable ablative silicone composition with viscosity within the suitable range discussed above can be produced, and the composition can be pumped through a suitable hose system to a spray gun or applicator, and then applied on target substrate in step (II).Furthermore, the use of high shear mixer in step (I) to prepare results in a much more thixotropic coating after application on substrate surface.
[0080] The hose system can include a main hose of suitable length and diameter, such as a minimum length of about 6 m and a diameter of about 1 cm to 1.5 cm, and, if desired, a more easily handled whip-type hose that makes it easier to connect the main hose to the spray gun / applicator, operate the spray gun / applicator, and apply the silicone ablative coating onto the desired substrate surface. The whip-type hose can be, for example, 2 or 3 meters long and of a similar but typically narrower diameter, such as 0.5 cm to 1 cm in diameter. In one embodiment, the minimum pressure at the spray gun was at least 3800 psig (26.2 MPa), or even 4000 psig (27.58 MPa).
[0081] The one-part room temperature curable and sprayable ablative silicone composition provided herein can be applied using any suitable spraying technique. For example, it can be applied on the substrate surface in the form of a fine airless atomized spray, and the resulting spray droplets coalesce on the substrate surface to form a continuous film, gradually increasing in thickness. Alternatively, the ablative coating composition can be applied via a textured type spray gun, where a much thicker coating is sprayed (or sputtered) on the substrate surface. If desired, the user can apply by another means, for example, by rolling, troweling, painting, alternative means, for example, by rolling, troweling, painting, or even by dip coating, but it will be understood that spray coating is considered to be particularly beneficial given the substrate to which such coating is applied.
[0082] The ablative coating compositions described herein are preferably applied onto a substrate surface that has been pre-cleaned, for example, with a suitable solvent that removes oils and other contaminants that may be present. Additionally, if desired or preferred, the substrate to be treated with the coating compositions described herein may be pre-treated with a suitable primer that can increase the substrate surface energy and material wetting, thereby improving adhesion. Any suitable primer can be utilized, for example DOWSIL™ 1200 RTV Prime Coat, available from Dow Silicones Corporation. If utilized, the primer should be applied very lightly and evenly by wiping, dipping, or spraying onto the pre-cleaned substrate surface. Gentle heating can be used to accelerate the cure rate of the primer. Typically, and especially when applied by spraying, it has been found that the ablative coating compositions described herein generally do not require pretreatment of the substrate with such a primer, since the compositions provide primerless adhesion to most substrates. In fact, the use of such a primer should not provide any significant improvement in the ablative adhesion profile of the ablative composition as described hereinabove to substrate surfaces after priming both steel and concrete substrates. In each case, adhesion results should be very similar after application of the ablative composition to the primed and unprimed substrate surfaces, with results in all four cases ranging from 0.35 kN / m to 5.25 kN / m according to Dow Silicones Corporation corporate test method (CTM) 0293, which is publicly available upon request.
[0083] Regardless of the method by which the coating is applied, the composition is designed to form a thixotropic coating on the substrate surface of a thickness suitable for the ablative coating. The thixotropy of the coating is observed almost immediately after application, and the coating can be built up to, for example, 2.5 mm to 5 mm thickness, or 2.5 mm to 4.45 mm thickness, without any significant flow / slump / creep behavior being observed. The ability to provide such coating thickness in a single application and not actually lose a significant amount of coating depth upon curing provides a significant advantage over conventional ablative coating compositions that rely on dilution effects to allow sprayability. This is especially true when considering that while a single coating layer may cure slower than other systems, diluted coatings require several coats to be applied, requiring approximately 12 hours between each coating application, and therefore may require several days to complete the coating process. The present coating composition can provide the user with a working time of up to 45 minutes, for example, 10 to 45 minutes, alternatively 10 to 30 minutes, alternatively 10 to 25 minutes, or alternatively 10 to 20 minutes. When the coating composition is sprayed onto a substrate, where the coating thickness can be significantly thinner than by other application methods, the working time tends to be shorter. However, when sprayed well onto the substrate surface, such a coating should not actually require working time, unlike when applied by other methods, such as troweling. Thus, the coating composition of the present invention can provide a relatively short skin over time (i.e., the point at which the uncured ablative composition does not move when touched) of 10 to 45 minutes, or less than 30 minutes, such as 10 to 30 minutes, or 10 to 25 minutes, or 10 to 20 minutes. The skin over time is often slightly shorter than the tack free time, since the skin may remain slightly tacky for a short period of time after the skin over time is met. The compositions herein provide a suitable deep cure after 24 hours.
[0084] Ablative coatings made from the one-part room temperature curable and sprayable ablative silicone compositions described herein can be used to coat any suitable substrate that is exposed to high heat, direct or indirect flame impingement and / or significant friction (i.e., hypersonic missiles).As discussed above, the articles in which the substrate forms a part may include aerospace vehicles, rocket parts such as nozzle units, combustion chambers and engine casings, reentry spacecraft, missile parts such as missile nose cones, missile and rocket launch pad aircraft parts, heat shields and / or other articles containing critical structural members associated with heat generating devices such as steel structures, cement trenches, etc. EXAMPLES
[0085] All viscosity measurements were made using a Brookfield™ DV-II+Pro programmable viscometer using spindle 7 at a shear rate of 10 rpm unless otherwise indicated. Viscosity measurements were made at 25° C. unless otherwise indicated.
[0086] In a first series of comparative examples, a series of proven comparative examples was prepared.
[0087] [Table 1]
[0088] In each case, each composition was found to be shear thinning.
[0089] The ingredients used in the compositions of Table 1 included the following: Polymer 1 is a methoxysilylethylene terminated polydimethylsiloxane having a viscosity of 2600 mPa.s at 25° C.; Precipitated calcium carbonate is commercially available from Specialty Minerals Inc., with a median particle size of 70 nanometers and a median diameter of 19 nm. 2ULTRA-PFLEX™, a hydrophobically treated precipitated calcium carbonate having a surface area of 0.1 g / g (supplier information); Ground calcium carbonate 1 is commercially available from Specialty Minerals Inc. and has an average particle size of 5.5 μm and 2 mm. 2 PFINYL™ 402, a hydrophobically treated ground calcium carbonate having a surface area of 1 / g (supplier information); Ground calcium carbonate 2 is commercially available from Imerys SA, has an average particle size of 3 μm and 3.5 μm. 2 Gama-Sperse™ CS-11, a hydrophobically treated ground calcium carbonate having a surface area of 1 / g (supplier information); The titanate catalyst is Tyzor™ PITA-SM ethylacetoacetate complex of titanium in methyl-trimethoxysilane, commercially available from Dorf Ketal Specialty Catalysts LLC; Polymer 2 is a dimethylhydroxy-terminated polydimethylsiloxane having a viscosity of 13,000 mPa.s at 25° C.; and Polymer 3 was a trimethyl-terminated polydimethylsiloxane having a viscosity of 100 mPa.s at 25°C.
[0090] The compositions shown in Table 1 were prepared as follows. Preparation of Comparative Example 1 (C.1) In a one gallon (4.55 liter) mixing vessel of a low shear bench mixer, 649.1 grams (g) of Polymer 1 was mixed with 30.0 g of methyltrimethoxysilane (crosslinker), 27.6 g of catalyst, and 1.7 g of N-(3-(trimethoxysilyl)propyl)-1,2-ethanediamine (adhesion promoter). The mixture was mixed at 20 rpm for 3 minutes. Subsequently, 439.0 g of precipitated calcium carbonate was introduced and the mixture was mixed for an additional 5 minutes at 45 rpm. Then, 859.2 g of ground calcium carbonate 2 was added and the mixture was mixed for 5 minutes at 45 rpm. After this, the mixture was further mixed at 60 rpm for 10 minutes, after which a second addition of 393.5 g of Polymer 1 was added and mixed for 5 minutes at 60 rpm. The mixture was then further mixed at 60 rpm for 10 minutes under a vacuum of 33589 Pascals (0.336 atm). The resulting composition was then packaged in 300 mL cartridges.
[0091] Preparation of Comparative Example 2 (C.2). 108.2 g of polymer 1, 5.0 g of methyltrimethoxysilane, 4.6 g of catalyst and 0.3 g of N-(3-(trimethoxysilyl)propyl)-1,2-ethanediamine were mixed together in a 400 mL dental cup at 800 rpm for 30 seconds. Then, 73.2 g of precipitated calcium carbonate was introduced and the resulting mixture was mixed at 2000 rpm for 30 seconds. Then, 143.2 g of ground calcium carbonate 2 was added and the resulting mixture was mixed at 2000 rpm for 30 seconds. Finally, 65.6 g of polymer 1 was introduced and the resulting mixture was mixed at 2000 rpm for 30 seconds. The samples were then packaged in 300 mL cartridges.
[0092] Preparation of Comparative Example 3 (C.3). 649.1 g of Polymer 1, 60.0 g of methyltrimethoxysilane, 20.4 g of catalyst, and 1.7 g of N-(3-(trimethoxysilyl)propyl)-1,2-ethanediamine were introduced into the mixing vessel of a 1 gallon low shear bench mixer and mixed together for 3 minutes at 20 rpm. 720.0 g of precipitated calcium carbonate was then introduced and the resulting mixture was mixed for 5 minutes at 45 rpm. 578.2 g of ground calcium carbonate 1 was then introduced and mixed for 5 minutes at 45 rpm. The mixing speed was then increased to 60 rpm and mixed for 10 minutes. Finally, an additional 370.7 g of Polymer 1 was introduced and mixed for 5 minutes at 60 rpm. Mixing was then continued for 10 minutes at 60 rpm under a vacuum of 33,589 Pascals (0.336 atm). The material was then packaged into 300 mL cartridges.
[0093] Preparation of Development Example 1. 108.2 g of Polymer 1, 10.0 g of methyltrimethoxysilane, 3.4 g of catalyst and 0.3 g of N-(3-(trimethoxysilyl)propyl)-1,2-ethanediamine were blended together in a 400 mL dental cup for 30 seconds at 800 rpm. Then 120 g of precipitated calcium carbonate was added and mixed for 30 seconds at 2000 rpm. Then 96.4 g of ground calcium carbonate 1 was introduced and mixed for 30 seconds at 2000 rpm. Finally, 61.8 g of Polymer 1 was introduced and mixed for 30 seconds at 2000 rpm. The samples were then packaged in 300 mL cartridges.
[0094] Preparation of Development Example 2. 649.1 g of polymer 1, 60.0 g of methyltrimethoxysilane, 20.4 g of catalyst, and 1.7 g of N-(3-(trimethoxysilyl)propyl)-1,2-ethanediamine were introduced into the mixing vessel of a 1 gallon (4.55 liter) high shear bench mixer and mixed with the slow anchor blade at 50 rpm for 3 minutes. 720.0 g of precipitated calcium carbonate was then introduced and mixed with the slow anchor blade at 100 rpm and then mixed with the single high speed mixing blade at 5000 rpm for 5 minutes. 578.2 g of ground calcium carbonate 1 was then introduced and mixed with the slow anchor blade at 100 rpm and then mixed with the single high speed mixing blade at 5000 rpm for 5 minutes. The mixing speed of the high speed mixing blade was then increased to 7000 rpm and the mixture was mixed for an additional 20 minutes. Finally, 370.7 g of polymer 1 was introduced and mixed with a low speed mixing blade at 100 rpm, then with a single high speed mixing blade at 4000 rpm for 5 minutes. Mixing was then continued under a vacuum of 33,589 Pascal (0.336 atm) for 10 minutes. The material was then packaged in 300 mL cartridges.
[0095] Preparation of Comparative Example 4. 480.0 g of Polymer 2, 240.0 g of Polymer 3, 30.0 g of methyltrimethoxysilane, 27.6 g of catalyst, and 1.7 g of N-(3-(trimethoxysilyl)propyl)-1,2-ethanediamine were placed in the mixing vessel of a 1 gallon (4.55 liter) low shear bench mixer. The mixture was mixed for 3 minutes at 20 rpm. 439.0 g of precipitated calcium carbonate was then introduced and mixed for 5 minutes at 45 rpm. 859.2 g of ground calcium carbonate 2 was then introduced and mixed for 5 minutes at 45 rpm. The mixing speed was then increased to 60 rpm and the mixture was mixed for an additional 10 minutes. Finally, 321.8 g of Polymer 1 was introduced and mixed for 5 minutes at 60 rpm. The composition was then further mixed for 10 minutes at 60 rpm under a vacuum of 33,589 Pascals (0.336 atm). The material is then packaged into 300 mL cartridges.
[0096] The samples were then tested for their extrusion rate (according to ASTM C 1183).
[0097] Flow / Sag / Slump (measured according to ASTM C 639) and skin over time (SOT). SOT was measured in a similar manner to ASTM C 679, but instead of using strips of PE film, skin over time was determined as the time it took for the coating to become tack-free when touched with a bare fingertip. The results are shown in Table 2.
[0098] [Table 2]
[0099] Comparative Examples 1 and 2 C.1 was prepared using a low shear method. C.2 was prepared in a high shear dental mixer, but produced poor slump. Both C.1 and C.2 compositions were very fluid and showed little thixotropic behavior, regardless of the preparation technique used.
[0100] Comparative example 3 (C.3) Despite having a similar composition to Development Example 1, Comparative Example 3 (C.3) When prepared using a low shear bench mixer it exhibits poor thixotropic behavior.
[0101] Development Examples 1 and 2 These were prepared using a high shear mixer. On the other hand, they show significantly better thixotropic behavior, as evidenced by the slump measurements for D.2, which was prepared using a high shear dental mixer. Development Examples 1 and 2 showed the need to mix using high shear mixing. 12 batches were split into two buckets in a high shear batch mixer. The samples were sprayed onto a vertical wall, applying a coating up to about 19 mm, with minimal flow / slump visible. However, while providing the required thixotropy and not having flow / slump problems, they were unfortunately found to have too high a viscosity and therefore could not be pumped through a suitably long hose system.
[0102] A second series of examples was then prepared in which the sample of D.1 above was prepared along with five additional samples, the compositions of which are shown in Table 3 below.
[0103] [Table 3]
[0104] D.3, D.4 and inventive examples 1-3 (IE.1-IE.3) were all prepared using a twin screw extruder. All extrusion experiments were carried out on a modular 25 mm co-rotating fully intermeshing twin screw extruder manufactured by Krupp Werner and Pfleiderer (Coperion). The extruder is driven by a 21.5 kW AC motor with a flux vector drive capable of generating screw speeds up to 1200 rpm. The actual diameter of each screw is 25 mm and the channel depth is 4.15 mm. The cross-sectional area of the free space is 3.2 cm 2 The machine had a length to diameter ratio of 48:1 L / D (12 barrels) with a total free process volume of 0.384 liters. The screw elements used consisted of a right-handed conveying screw and a left-handed conveying screw and a kneading block.
[0105] The resulting compositions were then tested for their final viscosity using a Brookfield™ DV-II+Pro programmable viscometer at a shear rate of 10 rpm with spindle 7. The coating thickness achieved before slump / flow (mm) occurred was determined using a wet film comb and is an average value. The results for each sample are shown in Table 4.
[0106] [Table 4]
[0107] Development Example D.3 was essentially the same composition as D.1, but made in a twin screw extruder rather than a high speed mixer. When tested for extrusion rate, it showed a slight improvement in extrusion rate compared to the original D.1.
[0108] In the case of D.3, D.4 and inventive examples IE.1 to IE.3, samples were prepared with the aim of modifying the composition until an optimized composition was prepared which gives a suitable pumpable composition (i.e. having a viscosity low enough to allow the uncured composition to be transported through a hose apparatus and sprayable using a suitable spray gun such that a substrate can be coated with the one-part room temperature curable and sprayable ablative silicone composition herein in a single coating of a suitable coating thickness, for example 2.5 mm to 5 mm, alternatively 2.5 mm to 4.45 mm thick, which is achieved in the case of IE.1 to IE.3).
[0109] The coating thickness achieved before slump / flow (mm) was determined using a wet film comb gauge and is an average value, ranging from 2.5 mm to 4.45 mm for the inventive examples.
[0110] IE.2 was tested for deep cure using in-house test method CTM 0663, which is publicly available on request, and was found to have cured to about 0.28mm after 24 hours, which was considered satisfactory.
[0111] To provide evidence of good physical properties of the cured ablative coating material designated IE.2, physical property tests were conducted and the results are shown in Table 5 below.
[0112] [Table 5]
[0113] Shore A hardness was measured according to ASTM D2240 Tensile strength, elongation at break and modulus at 100% elongation were measured according to ASTM D412.
[0114] Additionally, the ablative properties of IE.2 were compared to those of Comparative Example 4 (Comp.4). As discussed above, to accomplish this, the coating was exposed to an acetylene-oxygen torch. The torch was a rosebud tipped torch using an oxyacetylene mixture resulting in a torch output temperature of approximately 3500° C. For all experiments shown in Table 6, the torch was held approximately 0.75 inches (1.9 cm) from the ablative coating surface during testing.
[0115] The substrates used were ceramic tile specimens, and the ablative coating thickness for each sample was typically 2.9-3.5 mm thick.
[0116] penetration rate Each of the ablative coatings of C.4 and IE.2 was applied to a substrate surface and cured. The penetration percentages shown in Table 6 were averaged over 10 samples. The penetration percentage was determined for each sample by exposing the sample to the torch for 10 seconds, taking thickness measurements of the substrate and coating using a set of calipers prior to the period of exposure to the lamp, exposing the coating to the torch for 10 seconds, and re-measuring the thickness of each sample after exposure to the torch. The difference was then divided by the exposure time to obtain the penetration percentage.
[0117] Bulk Weight Loss Each of the ablative coatings of C.4 and IE.2 was applied to a substrate surface and cured. The bulk weight loss was measured by determining the weight of the coating and substrate before exposure to the torch, reweighing after 10 seconds of exposure to the torch, and determining the difference.
[0118] Duration of exposure Each of the ablative coatings of C.4 and IE.2 was applied to a ceramic tile surface and allowed to cure. The resulting coating was exposed to a torch until the sample coating was compromised, i.e., no further coating was present on the substrate at the time of exposure.
[0119] The results are reported in Table 6.
[0120] [Table 6]
[0121] It will be seen that Example IE.2 herein gave an improved response to the test when compared to C.4.
Claims
1. 1. A method for providing an ablative coating to a substrate, comprising: (I) preparing a one-part, room temperature curable, sprayable, ablative silicone composition by high shear mixing in a high shear mixer and / or using a twin screw extruder, said one-part, room temperature curable, sprayable, ablative silicone composition comprising: (a) an organopolysiloxane having the following structure: D-Z-(R 1 ) y SiO (4-y)/2 ) z -SiR 1 2 -Z-D (Wherein D is (i) -Si-R n X 3-n or (ii) -Si(R 1 ) 2 -O-Si(R 1 )(O-Si(R 1 ) 2 -Z 1 -Si-R n X 3-n ) 2 Either Each R 1 are the same or different and are an alkyl group, an alkenyl group, or an aryl group; 1 is a divalent organic group, y has an average value of about 2, z is the number average degree of polymerization and is an integer of at least 50, each X is a hydroxyl group or an alkoxy group, each R is individually selected from alkyl groups, aminoalkyl groups, polyaminoalkyl groups, epoxyalkyl groups, alkenyl groups, or aromatic groups, and n is 0, 1, or 2; (b) At least 15 m, which can be hydrophobized. 2 / g BET surface area of precipitated calcium carbonate; (c) one or more non-fibrous, non-reinforcing fillers; and wherein the cumulative weight percentage of components (b) and (c) is from 40 to 60 weight percent of said composition, and the weight ratio of said precipitated calcium carbonate (b) to said one or more non-fibrous, non-reinforcing fillers (c) is from 1:2 to 1:
7. (d) a silane crosslinker having the structure R 7 c -Si-R 6 4-c (In the formula, each R 7 is an alkoxy group, a ketoximino group, or an alkenyloxy group having 1 to 10 carbons, and each R 6 is selected from nonhydrolyzable silicon-bonded organic groups, and c is 2, 3, or 4; (e) a titanate or zirconate condensation reaction catalyst; the composition is substantially free of diluents or solvents; and preparing said one-part room temperature curable and sprayable ablative silicone composition resulting from step (I) having an extrusion rate of 1900 to 2600 g / min, as measured according to ASTM C1183; (II) spraying the resulting mixture of step (I) onto a substrate surface to produce a thixotropic, curable coating on said substrate having a coating thickness of 2.5 to 5 mm as measured using a wet film comb gauge before any visible indication of slump / flow occurs; (III) curing the composition at room temperature.
2. 10. The method for providing an ablative coating to a substrate as recited in claim 1, wherein said one or more non-fibrous, non-reinforcing fillers of component (c) is ground calcium carbonate.
3. 3. The method for providing an ablative coating to a substrate according to claim 1 or 2, wherein the high shear mixer is a twin screw extruder.
4. 4. The method for providing an ablative coating on a substrate according to any one of claims 1 to 3, wherein the one-part, room temperature curable and sprayable ablative silicone composition resulting from step (I) has a viscosity of 40 Pa s to 125 Pa s using a Brookfield™ DV-II+ Pro programmable viscometer using spindle 7 at a shear rate of 10 rpm measured at 25°C.
5. 5. The method for providing an ablative coating on a substrate according to any one of claims 1 to 4, wherein during step (III), the one-part room temperature curable and sprayable ablative silicone composition cures such that the ablative coating cures at a rate such that the depth of cure in 24 hours is between 0.25 cm and 0.6 cm.
6. 6. The method for providing an ablative coating on a substrate according to any one of claims 1 to 5, wherein the substrate is a steel structure, a cement trench, a rocket, a heat shield, a rocket engine, a missile, a missile nose cone, a missile deployment system, a spacecraft, an aerospace vehicle, a rocket part, a re-entry spacecraft, a missile part, a launch pad or an aircraft part.
7. 7. The method for providing an ablative coating on a substrate according to any one of claims 1 to 6, wherein the one-part, room temperature curable and sprayable ablative silicone composition prepared has a viscosity of 40 Pa·s to 100 Pa·s using a Brookfield™ DV-II+Pro programmable viscometer using spindle 7 at a shear rate of 10 rpm, measured at 25°C, and / or has an extrusion rate of 1900 to 2500 g / min, measured according to ASTM C1183, and / or the thixotropic curable coating on the substrate is provided at a coating thickness of 2.5 to 4.45 mm deep, measured using a wet film comb gauge, before any visible indication of slump / flow appears.
8. The high shear mixer is operated at a speed of at least 500 revolutions per minute or at least 3.25 ms. -1 8. A method for providing an ablative coating to a substrate according to any one of claims 1 to 7, operated at a tip speed of greater than
9. An article having an ablative coating obtainable or obtained by the process according to any one of claims 1 to 8.
10. 1. An article having an ablative coating that is the cured product of a one-part, room temperature curable, sprayable ablative silicone composition, said ablative silicone composition comprising: (a) an organopolysiloxane having the following structure: D-Z-(R 1 ) y SiO (4-y)/2 ) z -SiR 1 2 -Z-D (Wherein D is (i) -Si-R n X 3-n or (ii) -Si(R 1 ) 2 -O-Si(R 1 )(O-Si(R 1 ) 2 -Z 1 -Si-R n X 3-n ) 2 Either Each R 1 are the same or different and are an alkyl group, an alkenyl group, or an aryl group; 1 is a divalent organic group, y has an average value of about 2, z is the number average degree of polymerization and is an integer of at least 50, each X is a hydroxyl group or an alkoxy group, each R is individually selected from alkyl groups, aminoalkyl groups, polyaminoalkyl groups, epoxyalkyl groups, alkenyl groups, or aromatic groups, and n is 0, 1, or 2; (b) At least 15 m, which can be hydrophobized. 2 / g BET surface area of precipitated calcium carbonate; (c) one or more non-fibrous, non-reinforcing fillers; and wherein the cumulative weight percentage of components (b) and (c) is from 40 to 60 weight percent of said composition, and the weight ratio of said precipitated calcium carbonate (b) to said one or more non-fibrous, non-reinforcing fillers (c) is from 1:2 to 1:
7. (d) a silane crosslinker having the structure R 7 c -Si-R 6 4-c (In the formula, each R 7 is an alkoxy group, a ketoximino group, or an alkenyloxy group having 1 to 10 carbons, and each R 6 is selected from nonhydrolyzable silicon-bonded organic groups, and c is 2, 3, or 4; (e) a titanate or zirconate condensation reaction catalyst; the one-part, room temperature curable, sprayable ablative silicone composition is substantially free of diluents or solvents; and having an extrusion rate of 1900 to 2600 g / min, as measured according to ASTM C1183; and after spraying onto a substrate surface to produce a thixotropic curable coating on said substrate, the article has a coating thickness of 2.5 to 5 mm as measured using a wet film comb gauge before any visible indication of slump / flow appears.
11. 11. The article of claim 10, selected from a steel structure, a cement trench, a rocket, a heat shield, a rocket engine, a missile, a missile nose cone, a missile deployment system, a spacecraft, an aerospace vehicle, a rocket part, a reentry spacecraft, a missile part, a launch pad, or an aircraft part.
12. In preparing an ablative coating on a substrate, (a) an organopolysiloxane having the following structure: D-Z-(R 1 ) y SiO (4-y)/2 ) z -SiR 1 2 -Z-D (Wherein D is (i) -Si-R n X 3-n or (ii) -Si(R 1 ) 2 -O-Si(R 1 )(O-Si(R 1 ) 2 -Z 1 -Si-R n X 3-n ) 2 Either Each R 1 are the same or different and are an alkyl group, an alkenyl group, or an aryl group; 1 is a divalent organic group, y has an average value of about 2, z is the number average degree of polymerization and is an integer of at least 50, each X is a hydroxyl group or an alkoxy group, each R is individually selected from alkyl groups, aminoalkyl groups, polyaminoalkyl groups, epoxyalkyl groups, alkenyl groups, or aromatic groups, and n is 0, 1, or 2; (b) At least 15 m, which can be hydrophobized. 2 / g BET surface area of precipitated calcium carbonate; (c) one or more non-fibrous, non-reinforcing fillers; and wherein the cumulative weight percentage of components (b) and (c) is from 40 to 60 weight percent of said composition, and the weight ratio of said precipitated calcium carbonate (b) to said one or more non-fibrous, non-reinforcing fillers (c) is from 1:2 to 1:
7. (d) a silane crosslinker having the structure R 7 c -Si-R 6 4-c (In the formula, each R 7 is an alkoxy group, a ketoximino group, or an alkenyloxy group having 1 to 10 carbons, and each R 6 is selected from nonhydrolyzable silicon-bonded organic groups, and c is 2, 3, or 4; (e) a titanate or zirconate condensation reaction catalyst, 1. Use wherein the composition is substantially free of diluents or solvents in the preparation of an ablative coating on a substrate, and has an extrusion rate of 1900 to 2600 g / min, as measured in accordance with ASTM C1183, and after spraying onto a substrate surface to produce a thixotropic, curable coating on said substrate, has a coating thickness of 2.5 to 5 mm, as measured using a wet film comb gauge, before any visible indication of slump / flow appears.
13. 13. The use according to claim 12, wherein the one or more non-fibrous, non-reinforcing fillers of component (c) is ground calcium carbonate.
14. 14. The use according to claim 12 or 13, wherein the one-part room temperature curable and sprayable ablative silicone composition resulting from step (I) has a viscosity of 40 Pa s to 125 Pa s using a Brookfield™ DV-II+ Pro programmable viscometer using spindle 7 at a shear rate of 10 rpm measured at 25°C.
15. 15. The use according to claim 12, 13 or 14, wherein the substrate is a steel structure, a cement trench, a rocket, a heat shield, a rocket engine, a missile, a missile nose cone, a missile deployment device, a spacecraft, an aerospace vehicle, a rocket part, a reentry spacecraft, a missile part, a launch pad or an aircraft part.
16. 1. A one-part room temperature curable and sprayable ablative silicone composition comprising: (a) an organopolysiloxane having the following structure: D-Z-(R 1 ) y SiO (4-y)/2 ) z -SiR 1 2 -Z-D (Wherein D is (iii)-Si-R n X 3-n or (iv) -Si(R 1 ) 2 -O-Si(R 1 )(O-Si(R 1 ) 2 -Z 1 -Si-R n X 3-n ) 2 Either Each R 1 are the same or different and are an alkyl group, an alkenyl group, or an aryl group; 1 is a divalent organic group, y has an average value of about 2, z is the number average degree of polymerization and is an integer of at least 50, each X is a hydroxyl group or an alkoxy group, each R is individually selected from alkyl groups, aminoalkyl groups, polyaminoalkyl groups, epoxyalkyl groups, alkenyl groups, or aromatic groups, and n is 0, 1, or 2; (b) At least 15 m, which can be hydrophobized. 2 / g BET surface area of precipitated calcium carbonate; (c) one or more non-fibrous, non-reinforcing fillers; and wherein the cumulative weight percentage of components (b) and (c) is from 40 to 60 weight percent of said composition, and the weight ratio of said precipitated calcium carbonate (b) to said one or more non-fibrous, non-reinforcing fillers (c) is from 1:2 to 1:
7. (d) a silane crosslinker having the structure R 7 c -Si-R 6 4-c (In the formula, each R 7 is an alkoxy group, a ketoximino group, or an alkenyloxy group having 1 to 10 carbons, and each R 6 is selected from nonhydrolyzable silicon-bonded organic groups, and c is 2, 3, or 4; (e) a titanate or zirconate condensation reaction catalyst; the one-part, room temperature curable, sprayable ablative silicone composition is substantially free of diluents or solvents; and having an extrusion rate of 1900 to 2600 g / min, as measured according to ASTM C1183; and after being sprayed onto a substrate surface to produce a thixotropic curable coating on said substrate, the composition has a coating thickness of 2.5 to 5 mm as measured using a wet film comb gauge before any visible indication of slump / flow appears.
Citation Information
Patent Citations
Room temperature vulcanisable silicone compositions
WO2020263763A1